Polymer microfiber for sensor and laser applications / Ninik Irawati - Ninik, Irawati (2017)
Polymer microfiber devices have been attracting attention as a platform for manipulating light at the nanoscale. The high sensitivity of polymer microfibers to detect changes in the surrounding refractive index due to the large evanescent field propagating outside the microfiber can be utilized in various optical sensor and laser applications. In this thesis, the fabrication process of PMMA microfiber has been introduced using a direct drawing technique. The aim of this research is to establish a micro scale polymer optical fiber as a new sensor and laser technology which can create devices that are extremely small sized, ultra lightweight and have the potential to be manufactured at low cost. To enhance the performance of the sensing probe, PMMA microfibers were coated and doped with sensitive materials such as Zinc Oxide (ZnO) and Agarose gel for sensing different relative humidity (RH) levels. It is observed that the probe sensitivity improves due to the sensitive coating materials used. For instance, as the RH increases from 50% to 80%, the peak wavelength shifted against RH at a rate of 21.4 pm/% and 28 pm/%, and with a linearity of 98.36% and 98.83% for the un-doped PMMA and agarose doped PMMA microfiber, respectively. When the composite are exposed to an environment of humidity, rapid surface adsorption of water molecules occurs which changes its optical property. On the other hand, temperature sensor and laser applications have been proposed and demonstrated using CdSe QD doped PMMA microfiber. It is observed that the doping material managed to enhance the capabilities of generating, propagating, converting and modulating light at the microscale. For instance, a stable mode-locked Ytterbium-doped fiber laser operating at 1087.5 nm was successfully demonstrated with repetition rate of 12.6 MHz, maximum pulse energy of 1.1 nJ and output power of 14 mW.